Semantic and visual robotic navigation in human-centered environments - Indermun, Shival (Stellenbosch : Stellenbosch University, 2025)
Indermun, S. 2025. Semantic and visual robotic navigation in human-centered environments. Unpublished doctoral dissertation. Stellenbosch: Stellenbosch University [online]. Available: https://scholar.sun.ac.za/items/4a3c4077-ecbc-44de-aa64-ac12e4f81b61